Arabic shadow theatre, 1300-1900 a handbook - Guo, Li 1956- (Leiden ; Boston Brill, 2020)
"This handbook aims mainly at an analytical documentation of all the known textual remnants and the preserved artifacts of Arabic shadow theatre, a long-lived, and still living, tradition - from the earliest sightings in the tenth century to the turn of the twentieth century. The book consists of three main parts and a cluster of appendixes. Part One presents a history of Arab shadow theatre through a survey of medieval and premodern accounts and modern scholarship on the subject. Part Two takes stock of primary sources (manuscripts), published studies, and the current knowledge of various aspects of Arabic shadow theatre: language, style, terminology, and performance. Part Three offers an inventory of all known Arabic shadow plays. The documentation is based on manuscripts (largely unpublished), printed texts (scripts, excerpts), academic studies (in Arabic and Western languages), journalist reportage, and shadow play artifacts from collections worldwide"-- Provided by publisher.
Research. Arabic Shadow Theatre in Historical Sources -- Early Modern Scholarship -- New Researches -- Resources. Primary Sources: Manuscripts and Artifacts -- Repertoires. Medieval Arabic Shadow Plays: Ibn Dāniyāl and others -- Ottoman Egyptian Shadow Plays -- Late Ottoman and Early Modern Egyptian Plays -- Syrian and Levantine Plays -- North African Plays -- Epilogue: Notes from the Field. Arabic Shadow Theatre Today.
Includes bibliographical references and index.
Keywords: Shadow shows -- Arab countries -- History and criticism